Andrew of St. Victor, a twelfth century hebraist - Hadfield, G (1972)
﻿ The aim of this study is to examine the biblical commentaries of Andrew of St. Victor, abbot of Wigmore (d.1175), and to pay particular attention to his Jewish sources. Andrew wrote commentaries on most of the books of the Old Testament. His work can be divided into three groups: commentaries on the historical books, written before 1147; interpretations of the prophetical books, written shortly after c.1134; and his exposition of the Song of Songs, Proverbs and Ecclesiastes, written before 1161 or 1163. Ever since Miss Smalley's articles in the Rech.Théol.anc.méd. of 1938 and 1939 and her book, The Study of the Bible in the Middle Ages, the importance of Andrew as a commentator has been recognized, but the fact that his works exist in manuscript form only, apart from his commentaries on Ecclesiastes and Jonah, has prevented his writings from becoming more widely known. For this reason I originally intended to prepare an edition of a commentary on one of the Pentateuchal books. However, as it became clear that an edition would lose much of its value without an examination of the sources Andrew used, I decided to concentrate on the latter. The large number of his commentaries made it necessary, all the same, to select one or two for special study. The interpretations of Exodus and Isaiah were chosen, first because they were written during different periods of Andrew's life, thus making it possible to follow any changes in his exegetical method; and secondly because the different contents of these books present their commentators with different problems. [contined in text ...]